Deltex1 is inhibited by the Notch–Hairy/E(Spl) signaling pathway and induces neuronal and glial differentiation. Issue 1 (December 2015) - Cheng, Yi-Chuan; Huang, Yin-Cheng; Yeh, Tu-Hsueh; Shih, Hung-Yu; Lin, Ching-Yu; Lin, Sheng-Jia; Chiu, Ching-Chi; Huang, Ching-Wen; Jiang, Yun-Jin
Abstract Background Notch signaling has been conserved throughout evolution and plays a fundamental role in various neural developmental processes and the pathogenesis of several human cancers and genetic disorders. However, how Notch signaling regulates various cellular processes remains unclear. Although Deltex proteins have been identified as cytoplasmic downstream elements of the Notch signaling pathway, few studies have been reported on their physiological role. Results We isolated zebrafishdeltex1 (dtx1 ) and showed that this gene is primarily transcribed in the developing nervous system, and its spatiotemporal expression pattern suggests a role in neural differentiation. The transcription ofdtx1 was suppressed by the direct binding of the Notch downstream transcription factors Her2 and Her8a. Overexpressing the complete coding sequence of Dtx1 was necessary for inducing neuronal and glial differentiation. By contrast, disrupting Dtx1 expression by using a Dtx1 construct without the RING finger domain reduced neuronal and glial differentiation. This effect was phenocopied by the knockdown of endogenous Dtx1 expression by using morpholinos, demonstrating the essential function of the RING finger domain and confirming the knockdown specificity. Cell proliferation and apoptosis were unaltered in Dtx1-overexpressed and -deficient zebrafish embryos. Examination of the expression ofher2 andher8a in embryos with altered Dtx1 expression showed that Dxt1-induced neuronal differentiation did not require a regulatory effect on the Notch–Hairy/E(Spl) pathway. However, both Dtx1 and Notch activation induced glial differentiation, and Dtx1 and Notch activation negatively inhibited each other in a reciprocal manner, which achieves a proper balance for the expression of Dtx1 and Notch to facilitate glial differentiation. We further confirmed that the Dtx1–Notch–Hairy/E(Spl) cascade was sufficient to induce neuronal and glial differentiation by concomitant injection of an active form of Notch withdtx1, which rescued the neuronogenic and gliogenic defects caused by the activation of Notch signaling. Conclusions Our results demonstrated that Dtx1 is regulated by Notch–Hairy/E(Spl) signaling and is a major factor specifically regulating neural differentiation. Thus, our results provide new insights into the mediation of neural development by the Notch signaling pathway.